EMPLOYEES’ COMPUTER COMPETENCY: EVIDENCE FROM GOVERNMENT DEPARTMENT - Roseliza Hamid; Nik Sarina Nik Md Salleh; Sakinah Mat Zin; Muhammad Ridhwan Ripin; Khadijah Abdul Rahman; Noorazzila Shamsuddin (Journal of Islamic, Social, Economics and Development, 2023)
The advancement of technology requires people to adapt with the changes in the working environment. The workers need to be able to use computers in their daily life, so that they can speed up the process of completing tasks efficiently. It was reported that Malaysian labour productivity experienced negative growth in 2020 due to lack of understanding on ICT among employees. A brief survey at a government organization reveals that most of the staffs were incompetent in using computer efficiently. They are experiencing some issues with computer system such as security problems, storage disk error and backup files problems. Ultimately, these issues lead to decreasing of productivity among the staff. Therefore, the objectives of this study were to identify the level of computer competency, individual factor, training, and computer experience among employees and to measure the significant difference of gender on employees’ computer competency. As for the purpose of data collection, self-administered questionnaires were utilized by using stratified sampling. The results show that the level of computer competency, training and computer experience among employees were at a moderate level, while individual factors were found to be high. Additionally, it was found that no significant difference between male and female employees on computer competency. Based on the findings of the research, some practical suggestions have been put forward.